Restoration as Fabrication of Origins A Material and Political History of Italian Renaissance Art - de Riedmatten, Henri; Gaffo, Fabio; Jaccard, Mathilde (De Gruyter, 2023)
This publication aims to clarify the relationships between material restoration and politics in Italian Renaissance art by focusing on the question of origin as a foothold for political, patrimonial, and cultural identity. Rather than reinstating the objects' initial forms and meanings, restoration practices implied remodeling them according to new identity needs and thus transforming their material and aesthetic reality.